Political structure and the establishment of the palm oil culture in the rural space of the Brazilian Amazon - Monteiro Neto, Albertino; Santos Nahum, João; Bastos dos Santos, Cleison (Revista da ANPEGE, 2025)
The evolution of oil palm cultivation in the Amazon has been shaped by various political and economic forces, notably through the National Program of Production and Use of Biodiesel (NPPUB) and the Agroecological Zoning of Palm Oil (ZAE-Palm Oil). This study examines the roles of the State and companies in expanding and perpetuating oil palm in the region. Through literature review and fieldwork, three phases were identified: the experimental phase (1940-1970), the pre-NPPUB period (1970-2004), and the NPPUB period (2004-present). While integrating family farming into the palm oil chain has provided income and autonomy, it has also fostered land subversion for capital gain, causing dependency and tension between market interests and rural communities, challenging long-term sustainability.